The Stress-Responsive Alternative Sigma Factor SigB of Bacillus subtilis and Its Relatives: An Old Friend With New Functions - Rodriguez Ayala, Facundo; Bartolini, Marco; Grau, Roberto (Frontiers in Microbiology, 2020)
Alternative sigma factors led the core RNA polymerase (RNAP) to recognize different sets of promoters to those recognized by the housekeeping sigma A-directed RNAP. This change in RNAP promoter selectivity allows a rapid and flexible reformulation of the genetic program to face environmental and metabolic stimuli that could compromise bacterial fitness. The model bacterium Bacillus subtilis constitutes a matchless living system to study the role of alternative sigma factors in gene regulation and physiology. SigB from B. sultilis was the first alternative sigma factor described in bacteria. Studies of SigB during the last 40 years have shown that it controls a genetic universe of more than 150 genes playing crucial roles in stress response, adaption and survival. Activation of SigB relies on three separate pathways that specifically respond to energy, environmental and low temperature stresses. SigB homologs, present in other Gram-positive bacteria, also play important roles in virulence against mammals. Interestingly, during recent years, others unexpected B. subtilis responses, were found to be controlled by SigB. In particular, SigB controls the efficiencies of spore and biofilm formation, two important features playing critical roles for adaptation and survival in planktonic and sessile B. subtilis communities. In B. subtilis, SigB induces the expression of the Spo0E aspartyl-phosphatase responsible for the blockage of sporulation initiation. The upregulated activity of Spo0E interconnects the two predominant adaptive pathways (i.e., sporulation and stress response) present in B. subtilis. In addition, the RsbP serine-phosphatase, belonging to the energy stress arm of the SigB regulatory cascade, controls the expression of the key transcription factor SinR to decide whether cells residing in the biofilm remain in and mantain biofilm growth or scape to colonize new niches through biofilm dispersal. Finally, SigB intervenes in the recognition and response to surrounding microorganisms, a new SigB role, that could have agronomic impact. SigB is induced when B. subtilis is confronted with phytopathogenic fungi (e.g., Fusarium verticillioides) and halts fungal growth to the benefit of plant growth. In this review, we update the knowledge on the different regulatory networks controlling the activation of SigB and its new roles described during the recent years.